PENGEMBANGAN EKONOMI LOKAL YANG BERORIENTASI PADA PENYERAPAN TENAGA KERJA DI PROVINSI JAWA TIMUR - Eny Haryati (EKUITAS (Jurnal Ekonomi dan Keuangan), 2010)
Local economic development (LED) is an effort to optimize local resources involving government, business, local communities and civil society organizations to develop the economy in a region. Therefore the focus of LED include: increased local content, the involvement of stakeholders in a substantially economy, increase community resilience and economic independence, sustainable development, utilization of development by most local communities, small and medium enterprise development, economic growth achieved inclusively, strengthening capacity and improving the quality of human resources, reduction of disparities between groups of society, across sectors and across regions, reducing the negative impacts of economic activities on the environment. Study based on 4 (four) districts in East Java province is known that: (1) modern industrial sector is not likely to contribute to the gross regional domestic product and are less likely to absorb local labor force, (2) the agricultural sector contribute to the gross regional domestic product significantly and tends to absorb labor, (3) development of investment and/or industrialization should be oriented to the utilization of the potential and/or local resources and/or local labor, (4) to increase the market potential and/or to support the movement of investment and industrialization on the agricultural sector, need to develop the service sector; (4) the height of commitment from policy makers for investment and industrialization policy agenda based on local employment is much more important, (5) a commitment that needs to be realized in a policy of innovative and marketable.